1989
DOI: 10.4319/lo.1989.34.4.0718
|View full text |Cite
|
Sign up to set email alerts
|

Diel fluctuations in bacterial activity on streambed substrata during vernal algal blooms: Effects of temperature, water chemistry, and habitat

Abstract: Diel fluctuations in stream water temperature and chemistry, microbial biomass, and bacterial activity were measured in White Clay Creek, Pennsylvania, during vernal algal blooms in three different years. DOC concentrations increased 24-37% over early morning minima and temperature increased nearly 10°C over a 7-10-h period. Total carbohydrates and monosaccharides exhibited irregular fluctuations with total carbohydrates showing concentration peaks in the morning and afternoon. Acetate concentrations were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
153
4
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(162 citation statements)
references
References 62 publications
4
153
4
1
Order By: Relevance
“…Furthermore, the combination of elevated physical disturbance (e.g., hydrology) on microbial communities (Widder et al, 2014) upstream with the observation that postdisturbance recovery of specialists is less successful than for generalists (Clavel et al, 2011) may further contribute to the spatial patterns of functional traits we observed in this study. Finally, benthic algae which provide the bulk DOC source in streams above the treeline exude compounds, often monomeric in nature, that do not require specialised metabolic pathways and that are therefore readily available to a wide range of microbial heterotrophs (Kaplan and Bott, 1989). These combined effects may further contribute to the specialisation pattern that we observed along the study streams.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, the combination of elevated physical disturbance (e.g., hydrology) on microbial communities (Widder et al, 2014) upstream with the observation that postdisturbance recovery of specialists is less successful than for generalists (Clavel et al, 2011) may further contribute to the spatial patterns of functional traits we observed in this study. Finally, benthic algae which provide the bulk DOC source in streams above the treeline exude compounds, often monomeric in nature, that do not require specialised metabolic pathways and that are therefore readily available to a wide range of microbial heterotrophs (Kaplan and Bott, 1989). These combined effects may further contribute to the specialisation pattern that we observed along the study streams.…”
Section: Discussionmentioning
confidence: 57%
“…In alpine streams, autochthonous deliveries from algal production (and mosses) characterise DOC in streams above the treeline, whereas terrestrial deliveries increasingly add to the carbon pool further downstream (Battin et al, 2004;Milner et al, 2009;Zah and Uehlinger, 2001). Several studies have reported DOC source and composition as potential drivers of microbial community structure and functioning in streams (e.g., Kaplan and Bott, 1989;Sun et al, 1997;Peter et al, 2011) and in lakes (e.g., Crump et al, 2003;Judd et al, 2006). However, only few have studied the relationship between DOC characteristics and microbial functional traits in streams (McArthur et al, 1985;Koetsier et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…From these studies in relatively pristine low-nutrient streams, DO 15 N production represented no more than 10% of assimilated 15 N tracer. In addition, Kaplan and Bott (1989) found that labile constituents of DON (dissolved free amino acids) exhibited diel cycles associated with a vernal algal bloom in a stream draining an agricultural landscape (White Clay Creek, Pennsylvania). Our results from 15 streams indicate that instream DON production represented a median of 8-17% of total NO { 3 uptake and was therefore a potentially large transformation of N. By including the study of streams with varying nutrient status, our results refine our understanding of N cycling in headwater streams, where DON inputs have previously been assumed to be dominated by allochthonous sources (Aitkenhead- Peterson et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Because production of dissolved organic carbon (DOC) by in-stream processes can be significant (Kaplan and Bott 1989), DON production may also be significant in streams. Production of autochthonous dissolved organic matter (DOM, a portion of which is DON) by aquatic biota can occur through several mechanisms, including the release of cell constituents via death, senescence, viral lysis, or herbivory (Baines and Pace 1991;Bertilsson and Jones 2003), and these processes occur in both autotrophs (e.g., algae, macrophytes) and heterotrophs (i.e., bacteria, fungi).…”
mentioning
confidence: 99%
See 1 more Smart Citation